Fatigue failure analysis of cfrp composite laminates using modified stiffness degradation method - Azinan, Nabilah (2025)
Carbon fibre reinforced polymer (CFRP) composite laminates have been extensively utilised in various industrial applications due to their outstanding mechanical properties. In this study, the stiffness degradation behaviour of CFRP laminates subjected to cyclic loading conditions was analysed using two analytical models: the Modified Stage I model and the modified Stage I to Stage III model. Both models were developed based on the original model proposed by Lurie and Minhat, and subsequently enhanced through the introduction of several specific parameters to improve the predictive accuracy between analytical results and experimental data. The application of a linear elastic model facilitated the determination of the mechanical properties of the CFRP materials, which served as input parameters for the modified models. The modified Stage I model was employed to evaluate stiffness degradation during the initial damage phase, particularly matrix cracking. The resulting analytical stiffness degradation curves were compared with the experimental curves. Subsequently, the modified Stage I to Stage III model was applied to assess the full spectrum of stiffness degradation, encompassing damage evolution from the initial stage to the final stage, including fibre breakage. To evaluate the accuracy of both models, the percentage difference between the analytical model and experimental data was calculated for all three CFRP laminate configurations investigated in this study, namely [0,±45]s, [0,902]s, and [0,90,±45]s. Overall, the findings indicate that the Modified Stage I model offers the highest predictive accuracy when directly compared with experimental data, particularly for early-stage damage. The simplicity of its formulation and its strong agreement with empirical results render it highly effective and reliable for predicting fatigue-induced damage in the initial service life of the structure. However, to provide a more comprehensive representation of the material’s stiffness degradation behaviour throughout its service life, the modified Stage I to Stage III model presents a balanced compromise between predictive accuracy and the ability to capture the complete damage progression. Therefore, the selection of the most appropriate model should be guided by the intended application. For short-term assessments or early-stage damage monitoring, the Stage I model is the most suitable. Conversely, for long-term durability predictions involving comprehensive structural integrity evaluation, the Stage I to Stage III model is more appropriate, as it demonstrates a high level of accuracy and inclusiveness that closely aligns with experimental observations.